2020
DOI: 10.1186/s12889-020-8213-z
|View full text |Cite
|
Sign up to set email alerts
|

How men receive and utilise partner support when trying to change their diet and physical activity within a men’s weight management programme

Abstract: Background: The impacts of interventions designed to change health behaviours are potentially affected by the complex social systems in which they are embedded. This study uses Scottish data to explore how men receive and utilise partner support when attempting to change dietary practices and physical activity within the context of Football Fans in Training (FFIT), a gender-sensitised weight management and healthy living programme for men who are overweight/obese. Methods: Separate semi-structured face-to-face… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…Family and partner support also differed by gender. Whilst family support facilitated of their adoption of healthy lifestyle choices in the male narrative-consistent with existing evidence of the positive influence wives can play on the lifestyle behaviours of men [71,72]. Family in the female narrative, characterised busy schedules of tasks, obligations, and the body image preferences of their husbands was described as a hinderance to the adoption of healthy lifestyle choices.…”
Section: Gender and Social Membershipsupporting
confidence: 56%
“…Family and partner support also differed by gender. Whilst family support facilitated of their adoption of healthy lifestyle choices in the male narrative-consistent with existing evidence of the positive influence wives can play on the lifestyle behaviours of men [71,72]. Family in the female narrative, characterised busy schedules of tasks, obligations, and the body image preferences of their husbands was described as a hinderance to the adoption of healthy lifestyle choices.…”
Section: Gender and Social Membershipsupporting
confidence: 56%
“…These gendered effects of the couple-based intervention may be further rooted in Chinese Confucian culture and traditional social roles [ 34 ]. Chinese men tend to emphasize their masculine traits and be less caring, while women mainly take the caregiver roles [ 35 ]. Our previous qualitative study on older Chinese couples with T2DM revealed that wives, regardless of their health status, were more actively involved in or fully responsible for taking care of their husband’s disease management, whereas husbands were less engaged in their wives’ care activities [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The developing evidence on men's experiences of practicing weight loss strategies together as part of a WMP indicates that, in comparison to mixed-sex environments, a gender-sensitive context vastly improves men's sustained engagement, behaviour change and overall sense of embodiment (Budden et al, 2020(Budden et al, , 2021Donnachie et al, 2017;Hunt et al, 2013Hunt et al, , 2020Lozano-Sufrategui et al, 2016). This work highlights the crucial role played by the masculine-affirming weight loss strategy of physical activity participation, to the extent that men involved in gender-sensitive WMPs view the prospect of exercising with a female partner as inconvenient and potentially detrimental to their masculine independence (Tripathee et al, 2020). In respect of the mechanisms behind men's prolonged engagement and sense of healthful and masculine embodiment realised through being physically active with other men, negotiating the overlaps and tensions between masculine capital and hegemonic masculinity is considered integral (Budden et al, 2020;Hunt et al, 2013).…”
Section: Men Losing Weight Togethermentioning
confidence: 94%